Economic Geology of the Tumpa Gold Deposit (New California) - Tumialán de la Cruz, Pedro Hugo (1999)
The Tumpa gold deposit, operated by Cia. Minera Nueva California, located on the western flank of the Cordillera Blanca; It is a vein located between the intensely argilized granodiorite of the Cordillera Blanca batholith and a silicified andesitic dam. The mineralizing flow in its upper part was horizontal with a higher concentration of gold. The vein and dike were cut into 3 parts according to their direction by 2 similar faults to the vein and dike, of dip contrary to these structures; they have intense oxidation.